Manajemen Dakwah BKSPPI Dalam Mengembalikan Khittah Pesantren - Rosyadin, Isma; Zahrotunni'mah, Zahrotunni'mah (Komunika: Journal of Communication Science and Islamic Dakwah, 2021)
This study aims to find out and explain about the preaching management of the Indonesian Boarding School Board of Cooperation (BKsPPI) in the work program for the development of Islamic da'wah and ukhuwah Islamiyah, in returning the pesantren khittah. Until now there are a very large number of pesantren with schools and different cultures, BKsPPI has come up with its program to strengthen friendship between pesantren and as a development of the physical aspects and curriculum of the pesantren. This study aims to 1) To find out the Management of Da'wah Board of Cooperation of the Indonesian Islamic Boarding School (BKsPPI) in the Da'wah and Islamiyah Development Program. 2) To find out what are the strengths and weaknesses in the Management of Da'wah BKsPPI in the Da'wah Development Program and Ukhuwah Islamiyah. This research was conducted from November 2017 to February 2018. This study used primary and secondary sources. Primary data is primary data through direct interviews with BKsPPI management informants and documents which are historical evidence. While secondary sources are through books, theses, articles. BKsPPI with Science Culture Strategy, Adab Cultural Strategy, Da'wah Cultural Strategy, Independent Cultural Strategy, Jama'i Charitable Culture Strategy perfects the pesantren spirit and is able to return the pesantren in its direction line, namely as an iqamatuddin institution, a struggle institution, an educational institution, as well as a service institution in the community. Abstrak Penelitian ini bertujuan untuk mengetahui dan menjelaskan tentang manajemen dakwah Badan Kerjasama Pondok Pesantren Indonesia (BKsPPI) pada program kerja pengembangan dakwah Islamiyah dan ukhuwah Islamiyah, dalam mengembalikan khittah pesantren. Sampai sekarang ini berdiri pesantren dengan jumlah yang sangat banyak dengan madzhab dan kultur yang berbeda, BKsPPI tampil dengan programnya untuk mempererat silaturahim antar pesantren serta sebagai pengembanganan dari aspek fisik dan kurikulum pesantren. Penelitian ini bertujuan 1) Untuk mengetahui Manajemen Dakwah Badan Kerjasama Pondok Pesantren Indonesia (BKsPPI) pada Program Pengembangan Dakwah Islamiyah dan Ukhuwah Islamiyah. 2) Untuk mengetahui apa yang menjadi faktor kekuatan dan kelemahan dalam Manajemen Dakwah BKsPPI pada Program Pengembangan Dakwah Islamiyah dan Ukhuwah Islamiyah. Penelitian ini dilakukan dari bulan November 2017 sampai dengan Februari tahun 2018. Penelitian ini menggunakan sumber primer dan sekunder. Data primer adalah data primer melalui wawancara langsung dengan narasumber pengurus BKsPPI dan dokumen yang merupakan bukti sejarah. Sementara sumber sekunder adalah melalui buku-buku, skripsi, artikel. BKsPPI dengan Strategi Budaya Ilmu, Strategi budaya Adab, Strategi Budaya Dakwah, Strategi Budaya Mandiri, Strategi Budaya Amal Jama'i menyempurnakan ghirah pesantren dan mampu mengembalikkan pesantren dalam garis haluannya yaitu sebagai lembaga iqamatuddin, lembaga perjuangan, lembaga pendidikan, sekaligus lembaga pelayanan pada masyarakat.